Coklat Sebagai Penurun Nyeri Dismenore Primer pada Siswi SMK Farmasi di Bandarlampung - Fauziah, Nur Alfi; Fara, Yetty Dwi; Handayani, Rizka (Universitas Aisyah Pringsewu (UAP) Lampung, 2019)
Chocolate contains magnesium which functions to enlarge blood vessels so as to prevent muscle spasms and blood vessel walls, Therefore magnesium functions to relieve dysmenorrhea or pain during menstruation. The purpose of this study was to determine the reduction in dysmenorrhea pain by giving chocolate. The method in this study is pre experimental with the type of one group pretest-posttest design research. The population in this study were all young women who experience dysmenorrhea with a sample of 30 young girls. Data analysis uses independent t-test. The results showed that the average pain before chocolate consumption was 4.47, and after chocolate consumption was 2.78. There is a difference before and after giving chocolate to young women at Kesuma Pharmacy Vocational School in Bandar Lampung in 2019, with a p-value of 0.001 (less than 0.05). It is expected to be an input for young women who experience dysmenorrhea pain in order to consume chocolate as an alternative to non-pharmacology as a reduction in dysmenorrhea pain.